2017
DOI: 10.5152/tjar.2017.04568
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Pulse Pressure Variation (PPV) Compared with Stroke Volume Variation (SVV) in Predicting Fluid Responsiveness

Abstract: Objective: Static monitors for assessing the fluid status during major surgeries and in critically ill patients have been gradually replaced by more accurate dynamic monitors in modern-day anaesthesia practice. Pulse pressure variation (PPV) and systolic pressure variation (SPV) are the two commonly used dynamic indices for assessing fluid responsiveness. Methods: In this prospective observational study, 50 patients undergoing major surgeries were monitored for PPV and SPV: after the induction of anaesthesia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…We are aware of the literature indicating that the absolute, isolated CVP readings might have only a weak correlation with the blood volume. Research has shown that systolic pressure variation (SPV), stroke volume variation (SVV), and pulse pressure variation (PPV) are better predictors of fluid volume (11)(12)(13). We noted a major decrease in CVP into the negative pressure range during spontaneous breaths during and after the HEMI stimulus.…”
Section: Discussionmentioning
confidence: 67%
“…We are aware of the literature indicating that the absolute, isolated CVP readings might have only a weak correlation with the blood volume. Research has shown that systolic pressure variation (SPV), stroke volume variation (SVV), and pulse pressure variation (PPV) are better predictors of fluid volume (11)(12)(13). We noted a major decrease in CVP into the negative pressure range during spontaneous breaths during and after the HEMI stimulus.…”
Section: Discussionmentioning
confidence: 67%
“…The prone position increases abdominal pressure, which results in reduced venous return and lung compliance. Yu et al reported that high predictability of PPV, remained as useful indices for guiding uid therapy in prone patients with minimal alterations in the optimal cutoff values to predict uid responsiveness [19]. Compared to the SVV, PPV does not require additional kits and can reduce the patients' nancial burden and the accuracy is similar [20].…”
Section: Discussionmentioning
confidence: 99%
“…CO monitoring is not sufficient to manage patients with complex haemodynamic disorders because absent knowledge of preloading and afterloading conditions. Besides SV, stroke volume variation (SVV) or arterial pulse pressure variation (PPV) induced by respiratory variation turned out to be a valid dynamic assessment of fluid responsiveness in mechanically ventilated patients [27,28]. Both invasive arterial wave monitoring and non-invasive stroke volume monitoring permit monitoring of PPV or SVV.…”
Section: Fluid Challenge Strategiesmentioning
confidence: 99%
“…Arterial pressure waveform analysis The Vigileo/FloTrac system provides real-time CO measurements by deriving SV from the arterial pressure waveform recorded from an arterial catheter without any calibration, a technique also called arterial pressure waveform analysis (APCO). On the basis of numerous data, age, gender and BSA, APCO provides information about SV, CI, SVV, PPV and systemic vascular resistance indexed for BSA (SVRI) [27,53]. Goal-directed therapy based on Vigileo/FloTrac system could improve haemodynamics and reduce the duration of respiratory support after cardiac surgery.…”
Section: Non-calibrated Systemsmentioning
confidence: 99%